2016
DOI: 10.1007/s12282-016-0746-8
|View full text |Cite
|
Sign up to set email alerts
|

Atypical femoral fracture after receiving antiresorptive drugs in breast cancer patients with bone metastasis

Abstract: BackgroundAtypical femoral fracture (AFF) occurs with minor trauma in patients receiving antiresorptive drugs such as bisphosphonate and denosumab. We hypothesized that patients with bone metastasis who receive higher doses of antiresorptive drugs tend to experience AFF more frequently. This study aimed to investigate the prevalence rate of AFF in patients receiving antiresorptive drugs for bone metastasis of breast cancer.MethodsBased on the database from our hospital, patients with breast cancer between Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Conversely, a lack of physical loading causes osteocytes to trigger osteoclastic bone resorption, adapting the skeleton to reduce weight and metabolic demands while maintaining sufficient strength to withstand the reduced loads. Treatments that prevent resorption to combat bone loss have been associated with atypical fracture [ 2 , 3 ]. Thus, the focus has shifted towards strategies favoring bone anabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a lack of physical loading causes osteocytes to trigger osteoclastic bone resorption, adapting the skeleton to reduce weight and metabolic demands while maintaining sufficient strength to withstand the reduced loads. Treatments that prevent resorption to combat bone loss have been associated with atypical fracture [ 2 , 3 ]. Thus, the focus has shifted towards strategies favoring bone anabolism.…”
Section: Introductionmentioning
confidence: 99%
“… 22 Since the application of antiresorptive drugs in these patients is also employed in long-term settings, this phenomenon is expected to become more and more apparent and common. 23 Furthermore, in a Phase III multicentre, randomized, double-blind, placebo-controlled trial, reporting data for 10-year treatment with denosumab in postmenopausal women with osteoporosis, two cases of atypical femoral fractures were identified. 24 In summary, other pharmacological treatments which decrease bone turnover apparently have the same consequences regarding the risk for this special fracture type.…”
Section: Pathogenesismentioning
confidence: 99%
“…27 As a relatively uncommon phenomenon, real-world AFF cases may go unrecognized, and retrospective cohort studies have indeed found subclinical stress reactions and undiagnosed clinical AFF. 20,28 Impending AFF may also be misinterpreted as bone metastases, and corresponding treatment with bone radiation can substantially weaken the area. Importantly, cortical bone metastases are rare 20 and should raise suspicion for AFF.…”
Section: Epidemiologymentioning
confidence: 99%
“…17 For bone metastases, evidence of beaking was apparent at an average onset of 48.4 months of BMA use in a matched cohort study. 28 This suggests that screening for radiographic signs of AFF by 4 years may be prudent, especially if the patient already undergoes routine imaging for oncologic or other indications. However, there is no standard surveillance guidance to evaluate the development of beaking or cortical changes for patients on prolonged therapy.…”
Section: Onsetmentioning
confidence: 99%